Peran Dukungan dan Hambatan Kontekstual Terhadap Adaptabilitas Karier pada Mahasiswa Tingkat Akhir - Karinda Ayu Tamari; Sari Zakiah Akmal (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2018)
A senior college student is an individual who is in a transition from college to work life. In this transition period, last-year college students need to prepare themselves to face difference role as a worker. Furthermore, the phenomenon of college students who do not always work in accordance to their majors getting more. Therefore, having high career adaptability is important skill for students. One of the important factor that can influence an individual's career choice is an external factor or can be called as a form contextual support and barrier. This research was conducted to find out the role of contextual support and barrier to career adaptability at final grade student in Jabodetabek. The study used a Career Adapt-Abilities Scale (CAAS) and Contextual Support and Barriers Scale (CSB). The subjects of this study were 270 college students in Jabodetabek, which obtained from quota sampling technique in each region is represented by 30 sample. The role of contextual support and barrier to career adaptability tested by simple regression. The results showed that contextual support participated for 14.5% of career adaptability (p <0.05). Meanwhile, contextual barriers felt by final-year college student are insignificant to career adaptability. Therefore, giving support to final-year college students is an intervention that can be given to improve their career adaptability.